Gremios empresariales y derecha chilena: redes de poder y propuestas programáticas de la Sociedad Nacional de Agricultura, 1952-1958 - Pablo Rubio Apiolaza; Xaviera Salgado Ferrufino (Les Cahiers ALHIM)
Considered the oldest republican Chile business unions, the Sociedad Nacional de Agricultura (SNA) is one of the stakeholders with greater political, economic and cultural influence in the chilean national history. Therefore, it is crucial to examine its proposals and the political and social and cultural networks that articulated. Historically, many business-including the SNA-, associations enjoyed a direct participation in state and were informally linked to partisan politics. In this article, proposals and actions carried out by this organization during the government of Carlos Ibáñez del Campo (1952-1958) are analyzed. In the context of a government that raised state intervention at different times of its term, and socio-economic indicators showed a stagnation of the national economy, the share of employers' associations intensified against the backdrop of "global crisis." To this end, publishing and newspaper “El Campesino” -officer of SNA- and other chilean newspapers, so to examine the changes of proposal and articulated strategy that agricultural associations and right-wing parties during the decade analyze complex 1950, when it gave rise to a historical cycle that ended in 1973.